Dynamic visualizations: A two-edged sword? - Lowe, Richard (Springer, 2013)
Advances in computer technology have greatly facilitated the generation of dynamic visualizations fuelling a growing preference for animated graphics over their static counterparts. Animated graphics have thus become the visualization of choice in fields as diverse as science and high finance. An assumption underlying this shift to animations is that their direct portrayal of dynamic information is inherently superior to its indirect depiction in a static graphic. However, any benefits of animations must be offset against the costs that may be incurred due to psychological effects of their dynamics. Such problems are particularly likely in traditionally designed animations that depict the subject matter as an entire functioning system. However, alternative design approaches that are informed by the Animation Processing Model [R. Lowe and J-M. Boucheix. Learning from animated diagrams: How are mental models built? In Diagrammatic Representation and Inference, pp. 266–281, Springer, 2008.] offer a more effective way of presenting dynamic information. Viewers can be relieved of the burden of decomposing the whole dynamic system by presenting them instead with ready-made relation sets that are tailored to fit the perceptual and cognitive constraints of the human information processing system. Relation sets are designed to facilitate the internal construction processes that people use in composing mental models of the referent subject matter.